Biobased supramolecular ionic networks with optimized crystallinity and mechanical properties as promising dynamic materials for eutectogels design - Ronco, Ludmila Irene (2023)
Ionic supramolecular networks are attractive materials for technological applications with unique properties such as ionic conductivity, stimuli-responsiveness, recyclability, and self-healing. Herein, new semicrystalline supramolecular ionic networks are designed from fully biobased building blocks such as tartaric acid, phytic acid, sebacic acid, and a fatty dimer diamine (Priamine™ 1071). The combination of tartaric acid with Priamine™ 1071 results in a crystalline and brittle polymer, but its molecular regularity can be controlled by incorporating sebacic acid or phytic acid, affording tough materials with appropriate mechanical properties (elastic moduli ranging 19–42 MPa). Furthermore, the ionic polymers show network-to-liquid phase transitions between 75 and 127 °C, and in the liquid state, they were found to be miscible with a lithium-based deep eutectic solvent, yielding flexible and conductive eutectogels. Altogether, these dynamic networks could open new prospects for developing fully green soft ionic materials from their combination with other innovative and low-cost eutectic mixtures.